ANALISIS SWOT PADA USAHA UMKM FATHAN MANDIRI UNTUK MENINGKATKAN PEMSARAN PRODUK BERBASIS ELECTRONIC COMMERCE - Gilang Putra, Riyan Rinanda; Wahyuningsih, Sulis; Febrianti, Erlita (Jurnal Signaling, 2024)
This study aims to analyze internal and external factors that influence marketing strategies in the Fathan Mandiri MSME business using the SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. With the development of technology, electronic commerce-based marketing is one method that is expected to help MSMEs expand their markets and increase sales. Through a SWOT analysis, this study found that the strength of Fathan Mandiri MSMEs lies in good product quality and competitive prices. However, the weaknesses faced are the limited human resources who master technology and low brand awareness. Opportunities that can be utilized include the growth of the e-commerce market in Indonesia and government support for the digitalization of MSMEs. On the other hand, the threats faced are tight competition in the online market and changes in consumer preferences. Based on the results of the SWOT analysis, the strategic recommendations given are to increase human resource capacity in the use of technology, strengthen branding and promotion through e-commerce platforms, and take advantage of collaboration opportunities with third parties to expand marketing networks. Thus, Fathan Mandiri MSMEs are expected to be more competitive and develop in the digital era.